The taco cleanse : the tortilla-based diet proven to change your life - Allison, Wes (The Experiment, 2015)
The Taco Cleanse is an inexpensive and easy path to increased deliciousness, hunger reversal, and overall contentment: Eat tacos for every meal, adding margaritas as needed. It's that simple. Begin with a breakfast taco, the most important taco of the day. Even if you do nothing else, your mood will brighten in just 24 hours. Keep eating tacos and within a week your outlook will be noticeably improved. After 30 days, cleansers report lasting benefits--and you will too!